The Semantic Understanding of Contemporary Islamic Movements; A Case Study of the Sahwa Movement of Saudi Arabia - Davood Feirahi; reza hosseini (رهیافتهای سیاسی و بین المللی)
The present research has focused on main goal which is the semantic understanding of Sahwa Islamic movement in its early and later periods. Whereas complicated events and frequent changes are always happening in the Middle East, theoretical thinking is always lagging behind objective changes. Hereupon, this article attempts to understand the dynamics of the Sahwa Islamic Movement, which is less known to Iranians, using the Semantics as a theoretical framework according to Toshihiko Izutsu's thinking. In Semantics, the meaning is grasped through causal and inter-connection between words that ultimately leads to forming the semantic network. Using this, the transformation from the early Sahwa semantic network based on Political Islam during the 80th and 90th to the late Sahwa semantic network based on Civil Islam in the early 21st century is followable. This semantic transformation is causing of the transformation of the semantic worldview -according to Izutsu- of Sahwa from violence to tolerance. Research ahead follows this transformation in the interaction, which is occasionally complicated, between Sahwa scholars, official Wahhabi muftis, the Saudi royal family, and also Jihadi forces in the late three decades.